UJI DAYA HAMBAT EKSTRAK DAUN PANDAN WANGI (PANDANUS AMARYLLIFOLIUS ROXB) TERHADAP BAKTERI ESCHERICIA COLI - Siti Juariah; Melpasandy Melpasandy; Eli Yusrita (JURNAL MEDIA KESEHATAN, 2022)
Fragrant pandanus leaf plant (Pandanus amaryllifolius Roxb) contains antibacterial compounds such as flavonoids, alcolloids, saponins, and tannins. One alternative to overcome Escherichia coli bacterial infection is the use of fragrant pandanus leaves (Pandanus amaryllifolius Roxb). This study aims to determine the effectiveness of fragrant pandan leaf extract (Pandanus amarllyfolius Roxb) against the growth of Escherichia coli bacteria. This type of research is experimental using the disc diffusion method. Fragrant pandanus leaves are extracted by maceration method using ethanol 96% as a solvent. The results of the study found that the average diameter of the bland zone at a concentration of 25% is 6 mm, at a concentration of 50% is 11.7 mm, the concentration of 75% is 12.3 mm, at positive control (Chloramphenicol) is 25 mm, and negative control (ethanol 96%) is 6 mm. The conclusion of the study is the pandan leaves extract can inhibit the growth of bacteria Escherichia coli.